If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y * 3 = 0 Reorder the terms for easier multiplication: 3 * 3y = 0 Multiply 3 * 3 9y = 0 Solving 9y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '9'. y = 0 Simplifying y = 0
| 2(6x-4)=4(5x+3) | | 16y^2-3y+2.25=0 | | log(25x)-log(x-1)=2 | | 360=128+128+52+6x-8 | | -41+4x=79 | | log(b)=0.31 | | 5s+2r+6-3r-2= | | 2(4x-1)=3(3x-5) | | 8(-10x+21)=728 | | -32=0 | | -6c=-6 | | .4*x+150=x | | 180=5x-9+106+33 | | (X^2)*lnx=0 | | 6.25w=68.75 | | 16y^2-3y-16=0 | | -11x-7x+29=-14x+34 | | 3=8x+11+8 | | -7y+17-12y=-38 | | 1x-3+2x= | | x+14y+35=0 | | 16y^2-3y+16=0 | | 9-2n=29 | | s=4pier^2 | | 4/g-1=2 | | 4ln(2x+5)=12 | | a=-1.7+0.5b | | 3t-4s+1-t= | | -81=t+-5 | | z-24=31 | | 2w+-3=7 | | b+66=-25 |